2007 29th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2007
DOI: 10.1109/iembs.2007.4353650
|View full text |Cite
|
Sign up to set email alerts
|

Flexible dry surface-electrodes for ECG long-term monitoring

Abstract: In this paper a new generation of dry electrodes for ECG-recording purposes is presented. These electrodes are flexible, biocompatible, biostable and perform a dry signal acquisition without the use of any electrolyte gel or adhesive. Thereby no skin preparation is needed. The material properties allow integration into textiles to form intelligent clothes for long-term monitoring duties. The electrodes can be washed together with the carrier textiles and provide a very good wearing comfort resulting in wide ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 6 publications
0
57
0
Order By: Relevance
“…To overcome this, it is often reported that the electrodes should be applied some time prior to the tests, for example in [5,115]. This is to take advantage of the sweat generation underneath the electrode surface since sweat includes Author Material Construction method Beckmann et al [9] SS/silver/copper knit/weave/coating Marozas et al [65] silver plated nylon thread embroidery Hoffmann et al [43] carbon nano tubes foam Negru et al [79] carbon black coated weave Noury et al…”
Section: Design Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this, it is often reported that the electrodes should be applied some time prior to the tests, for example in [5,115]. This is to take advantage of the sweat generation underneath the electrode surface since sweat includes Author Material Construction method Beckmann et al [9] SS/silver/copper knit/weave/coating Marozas et al [65] silver plated nylon thread embroidery Hoffmann et al [43] carbon nano tubes foam Negru et al [79] carbon black coated weave Noury et al…”
Section: Design Considerationsmentioning
confidence: 99%
“…There are how-ever, several other modalities mentioned in the literature. A foam like electrode was created by Hoffmann et al [43]. The foam electrode was doped with carbon nano tubes and an electrolyte, which showed excellent properties of square resistance.…”
Section: Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally developed to replace off-the-shelf disposable gelled Ag/AgCl electrodes, the gold standard for clinical and short-term recording but limited by short operating time and poor comfort, traditional textile electrodes used without any conductive hydrogel failed to provide an effective way to access high-quality ECG signal [8]. High skin-electrode contact impedance, the consequently higher mains interference, the typically large baseline wandering artefact, the presence of the metal wires directly in contact with the skin, are the most remarkable problems associated to their use [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ECG signal was recorded using two moistened fabric sensors located at either side of the ribcage (Figure 1 (b)). The use of these fabric electrodes eliminates the requirement for adhesive electrodes which can be cumbersome to apply and have been shown to occasionally cause skin irritation [10], while also allowing for unlimited use. The ECG signal was recorded at a sampling rate of 250 Hz.…”
Section: B Protocol and Data Acquisition Systemmentioning
confidence: 99%